The Effectiveness of the Indonesian Forest Honeybee Conservation E-Module on Students' Environmental Literacy Ability - I Wayan Sumberartha; Mimien Henie Irawati Al Muhdhar; Deny Setiawan; Muhammad Iqbal Akbar; M. Nasir Tamalene; Wawan Suprianto Nadra; Alfian - Daud; Annisa Tullulu Kaunar; Lely - Mardiyanti (Jurnal Pendidikan Indonesia, 2021)
This study aims to analyze the effectiveness of the Indonesian forest honeybee conservation e-module on students' environmental literacy skills in natural resource management courses. This study uses a one-group pretest and posttest design. The sample in this study was 22 students of natural resource management class who were selected using the purposive sampling technique. The learning was carried out 5 times, starting with the pretest and ending with the posttest. The data collection instrument used a multiple-choice test of as many as 29 questions which were conducted online using google form. Data analysis using N-Gain Score. The results showed that the gain-score was 0.8. So, can be concluded that the effectiveness of the Indonesian forest honeybee conservation e-module is quite high in improving students' environmental literacy skills, especially in the aspects of ecological knowledge, conservation knowledge, the attitude in presenting data and information, scientific behavior (having curiosity and caring for the environment), and wise behavior and responsible.